The study of customer engagement of local sustainable fashion brands on Instagram content - Mayasari, Iin; Haryanto, Handrix Chris (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
The local enterprise aims to ensure long-term business continuity while enhancing brand awareness of regional businesses. Businesses use social media to boost customer engagement and local enterprise items that are ecologically friendly. This study intends to examine how local businesses' Instagram accounts for Local Sustainable Fashion Brands (LSFB) are used by their customers. This qualitative study examines brand engagement tactics used by LSFB and Instagram posts made by its followers. Content analysis is used in the analytical approach. In this study, the LFSB setting demonstrates how small business operators in the fashion industry have grown their enterprises. Social media usage to foster customer involvement is examined because it may assess the target market's brand recognition among a deluge of imported goods or worldwide brands.